2016
DOI: 10.1074/jbc.m116.731281
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin Protease Controls Copper and Cisplatin Accumulation via Cleavage of the Ctr1 Metal-binding Ectodomain

Abstract: Copper is an essential metal ion for embryonic development, iron acquisition, cardiac function, neuropeptide biogenesis, and other critical physiological processes. Ctr1 is a high affinity Cu ؉ transporter on the plasma membrane and endosomes that exists as a full-length protein and a truncated form of Ctr1 lacking the methionine-and histidine-rich metal-binding ectodomain, and it exhibits reduced Cu ؉ transport activity. Here, we identify the cathepsin L/B endolysosomal proteases functioning in a direct and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 67 publications
(66 reference statements)
0
51
1
Order By: Relevance
“…The removal of Asn 15 ‐linked glycan by mutation (N 15 Q) does not affect trafficking of the transporter to the cell surface . Several studies on EOC cells reported that the expression levels of CTR1 are not correlated to the amount of cDDP accumulation.17, Conversely, it has been reported that the elevation of CTR1 expression in the tumor cells increased their sensitivity to platinum drugs and the survival of cancer patients . We found that there is no significant difference in CTR1 expressions of A2780S and A2780CP cells (Figure C), the CTR1 expression is not changed in A2780S and A2780CP cells after cDDP‐treatment.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The removal of Asn 15 ‐linked glycan by mutation (N 15 Q) does not affect trafficking of the transporter to the cell surface . Several studies on EOC cells reported that the expression levels of CTR1 are not correlated to the amount of cDDP accumulation.17, Conversely, it has been reported that the elevation of CTR1 expression in the tumor cells increased their sensitivity to platinum drugs and the survival of cancer patients . We found that there is no significant difference in CTR1 expressions of A2780S and A2780CP cells (Figure C), the CTR1 expression is not changed in A2780S and A2780CP cells after cDDP‐treatment.…”
Section: Discussionmentioning
confidence: 60%
“…CTR1 on cell membrane is the most important cDDP‐transporting protein with the N‐linked glycosylation on its metal‐binding ecto‐domain . The colocalization of CTR1 with core fucosylation of N‐glycans on the cell membrane of ovarian carcinoma implied that the function of CTR1 may be correlated with core fucosylation in cDDP‐treated EOC (Figure D).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations